Glutathione-Induced Conversion of Pentavalent Antimony to Trivalent Antimony in Meglumine Antimoniate - Frézard, Frédéric (American Society for Microbiology, 2001)
The standard treatment of human leishmaniases involves the use of pentavalent antimony [Sb(V)] compounds, including meglumine antimoniate. The mode of action of these compounds has not been fully elucidated. The possibility that Sb(III) is involved has been suggested; however, the biomolecule that may induce the conversion of Sb(V) to Sb(III) has not yet been identified. In the present study, we investigated both the ability of reduced glutathione (GSH) to promote the reduction of Sb(V) into Sb(III) in meglumine antimoniate and the effects of pH and temperature on this transformation. GSH did promote the reduction of Sb(V) into Sb(III) in a dose-dependent manner. When GSH and meglumine antimoniate were incubated together at a GSH/Sb molar ratio superior or equal to 5:1, all antimony was encountered in the reduced form, indicating a stoichiometry of 5:1 between GSH and Sb(V) in the reaction. The reaction between Sb(V) and GSH was favored at an acidic pH (pH 5) and an elevated temperature (37°C), conditions found within the phagolysosome, in which Leishmania resides. For instance, about 30% of the Sb(V) (concentration, 2mM) was converted to Sb(III) following incubation for 3 days with 10 mM GSH at pH 5 and 37°C. Our data support the hypothesis that Sb(V) would be converted by GSH, or a related thiol compound, to more toxic Sb(III) in the phagolysosome of macrophages.